2009
DOI: 10.1128/jb.01458-08
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa PAO1 Pyocin Production Affects Population Dynamics within Mixed-Culture Biofilms

Abstract: Transcriptomic and phenotypic studies showed that pyocins are produced in Pseudomonas aeruginosa PAO1 aerobic and anaerobic biofilms. Pyocin activity was found to be high in slow-growing anaerobic biofilms but transient in aerobic biofilms. Biofilm coculture of strain PAO1 and a pyocin-sensitive isolate showed that pyocin production had a significant impact on bacterial population dynamics, particularly under anaerobic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 23 publications
1
74
0
Order By: Relevance
“…Based on these studies one would expect there to be more overlap between the transcriptomes of the anr and rsmA mutants, which suggests that experimental conditions may be crucial when using transcriptome profiling to study RsmA regulation. However, the RsmA regulatory profiles do exhibit substantial overlap with the profiles from microaerobic growth conditions in biofilms and in artificial sputum media (Fung et al, 2010;Waite & Curtis, 2009), whereby the transcriptional regulator PtxS, and genes associated with phenazine, PQS production and early biofilm formation, are modified in common. It has been reported that a subtle environmental difference can exert significant variation in the control of target genes of the Gac/Rsm pathway (Ventre et al, 2006), and therefore a fine balance can exist between positive and negative regulation of target genes by RsmA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these studies one would expect there to be more overlap between the transcriptomes of the anr and rsmA mutants, which suggests that experimental conditions may be crucial when using transcriptome profiling to study RsmA regulation. However, the RsmA regulatory profiles do exhibit substantial overlap with the profiles from microaerobic growth conditions in biofilms and in artificial sputum media (Fung et al, 2010;Waite & Curtis, 2009), whereby the transcriptional regulator PtxS, and genes associated with phenazine, PQS production and early biofilm formation, are modified in common. It has been reported that a subtle environmental difference can exert significant variation in the control of target genes of the Gac/Rsm pathway (Ventre et al, 2006), and therefore a fine balance can exist between positive and negative regulation of target genes by RsmA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the important question of whether oxygen availability influences the T3SS in P. aeruginosa remains to be addressed. While transcriptome analyses of the molecular response of P. aeruginosa to low oxygen have not yet identified any alteration in T3SS-associated gene expression (AlvarezOrtega & Harwood, 2007;Trunk et al, 2010), T3SS-associated gene expression is induced in anaerobic biofilms (Waite & Curtis, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…For example, stress-inducing conditions, such as anaerobic or oxidative stress, usually associated with pathogenesis in the lung, as well as mutagenic agents inducing production of all pyocin types but repressing expression of the S immunity [37][38][39][40]. It has also been speculated that the CF lung is an iron-limited environment [41], which can make cells more susceptible to S pyocin killing due to upregulated expression of ferri-pyoverdine and pyochelin receptors, which are required for iron uptake but also serve as receptors for S pyocins [2,42,43].…”
Section: (A) Bacteriocins and Strain Dominancementioning
confidence: 99%
“…Type R pyocins show broad similarities with the fibers of the tails of these phages. Type R pyocins are contractile and not flexible, the F type are flexible, but are not contractile; and the S type are susceptible to proteases (MichelBriand & Baysse, 2002;Waite & Curtis, 2009). The colicins are proteins between 29 and 90 kDa, which have binding, transport and specific activity domains, same as those found in pyocins.…”
Section: Amps From Gram Negative Bacteria and Their Classificationmentioning
confidence: 99%